Uso do índice RDE para determinação de anomalias de drenagem no Rio Capibaribe (PE) - Silva, Rubens Neves e; Gomes, Daniel Dantas Moreira; Lima, Carlos Eduardo Santos de; Goldfarb, Mauricio Costa (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
The longitudinal profile of a river is the Cartesian representation of the relationship between its height and its length. This relationship has been used as an important element for geomorphological and hydrological studies; example studies to determine the drainage anomalies. This study aimed to the determination and classification of river Capibaribe (PE) drainage anomalies. The analysis was made from the longitudinal profile of the Capibaribe river, built with the help of Google Earth software, through the RDE index proposed by Hack (1973). The longitudinal profile of the Capibaribe river is relatively balanced and contains anomalies second and first order. This profile presented an atypical geometry stretches in between kilometers 100 and 150, 150 and 200 and 200 and 250 due to the increase of the slope in the direction from upstream to downstream, as the literature indicates that in a typical profile should decrease in the slopes towards the mouth.